The role of GHRM practices towards organizational commitment: A mediation analysis of green human capital - Muhammad Shoaib; Zuhair Abbas; Muhammad Yousaf; Roman Zámeécník; Junaid Ahmed; Shahnawaz Saqib (Cogent Business & Management, 2021)
There are rare studies that have attempted to explore the association among green human resource management (GHRM) and organizational commitment in the existing literature. Besides, the mediating role of green human capital has also garnered little attention in the literature. Hence, the present study intends to address the research gap by extending the ability-motivation-opportunity theory (AMO) to determine the indirect and direct impact of GHRM in the dairy companies which has so far neglected in Pakistan. A convenience sampling technique was deployed to obtain data from 287 respondents through self-administered survey. SmartPLS (3.2.9) software was used to analyze the structural and measurement model. The results demonstrate the direct effect of green recruitment and selection and green training and development on organizational commitment. Also, green human capital contributes an essential role in mediating the effects of green recruitment and selection, green training, and development on organization commitment. The present study suggests that GHRM practices play a crucial role in the deployment of an environmental policy aimed at promoting green practices in the workplace. The findings provide guidelines to policymakers and managers regarding GHRM to promote environmental culture and employee green behavior at the workplace.
Keywords: M12; M53; M54; L66; 650; GHRM; organization commitment; green human capital; Pakistan; AMO theory